Makna Kesabaran dan Keikhlasan dalam Film Ayat-Ayat Cinta (2008) - Salman Hasyim Adz Dzikri; Irna Inayatul H; Rifa Taufik H; Rizal Firdaus; Dadan Firdaus Firdaus (Jurnal Teologi Islam, 2026)
This study examines the representation of Islamic spiritual values, specifically patience (ṣabr) and sincerity (ikhlāṣ), within contemporary visual media using Hasan al-Basri’s perspective of Akhlak Tasawuf. While previous studies on the film Ayat-Ayat Cinta (2008) predominantly focused on polygamy, feminism, or cultural commodification, this research addresses a critical academic gap by analyzing the film as a visual laboratory for internal spiritual transformations. Employing a qualitative descriptive approach with content analysis, data was collected through rigorous observation of dialogues and scenes, validated via source triangulation. The findings reveal that patience is represented as an active ethical response through three manifestations: ṣabr ’ala al-ta’ah, ṣabr ’ala al-musibah, and patience as the highest spiritual station (maqam). Concurrently, sincerity is depicted through horizontal, vertical, and transformative dimensions. These two pillars act as determinant factors in structuralizing the spiritual character development of the main character, Fahri. This study implies that popular cinema serves as an effective pedagogical vehicle for internalizing classical Sufi ethics among modern urban Muslim societies, bridging the bifurcation between classical Islamic texts and modern screen culture.